Hubungan Pengetahuan Kesehatan Reproduksi dengan Perilaku Hidup Sehat Ditinjau dari Jasmani, Rohani dan Sosial Siswa - sutarza, encep farlan; Juliantine, Tite; Fahri, Ahmad Syakur (Jurnal Sporta Saintika, 2023)
The purpose of this research was to determine the relationship of reproductive health knowledge with students' healthy behavior. The method used is quantitative descriptive with using correlational research. This research was conducted in high schools in the city of Bandung with a sample of 371 students, divided into 27 schools. The instrument used in this study using questionnaires knowledge of reproductive health and healthy behavior questionnaire. The results obtained are of reproductive health knowledge has a strong correlation with the healthy behavior of students in Bandung. Keywords: health reproduction, healthy life, students